Seizures in dogs and cats - Sanders, Sean (Ames, Iowa, USA : Wiley Blackwell, 2015)
'Offers a comprehensive, clinically oriented reference for treating canine and feline seizure patients'--Provided by publisher.
Includes bibliographical references and index.
Machine generated contents note: Chapter 1. Historical PerspectivesChapter 2. The Biology of SeizuresChapter 3. Epileptic Seizure Classification and SyndromesChapter 4. Client CommunicationChapter 5. DiagnosisChapter 6. Medical Management of SeizuresChapter 7. Anti-seizure MedicationsChapter 8. Emergency Management of SeizuresChapter 9. Alternative, Integrative and Complementary TherapyChapter 10. Advanced, Invasive Therapy for SeizuresAppendix I. Glossary of Descriptive Terminology for Veterinary Ictal SemiologyAppendix II. Clinical Neurology Forms and The Neurological ExaminationAppendix III. Online ResourcesAppendix IV. Anti-seizure Medication Formulary and Common Formulas.
Online resource; title from digital title page (viewed on June 02, 2015).
Keywords: Veterinary neurology; Dogs -- Diseases; Cats -- Diseases; Dog Diseases -- therapy; Seizures -- veterinary; Cat Diseases -- therapy; Electronic books